Sex differences in physical capacities of german bundesliga soccer players - de Araújo, M. C.; Baumgart, C.; Jansen, C. T.; Freiwald, J.; Hoppe, M. W. (The Journal of Strength and Conditioning Research, 2020)
Sex differences in physical capacities of elite soccer players have received limited attention. Therefore, this study investigated sex differences in linear and nonlinear sprint, squat and countermovement jump, core endurance, as well as incremental and intermittent endurance capacities in German Bundesliga soccer players. A total of 76 field players (29 women) were tested for the mentioned anaerobic- and aerobic-related physical capacities in a noninterventional cross-sectional design. The largest sex differences were evident in the explosive- and intermittent endurance-related capacities, with women presenting largely to extremely largely lower values in sprints, jumps, and intermittent endurance (effect size [ES] =1.77, p < 0.01). The differences in the total core endurance, running velocity at 2 and 4 mmol/L capillary blood lactate (v2 and v4), maximal heart rate (HR) (ES = 0.72, p = 0.06), and distance covered during the incremental endurance test (ES = 1.09, p = 0.01) were trivially to moderately lower for women. However, women had small to moderately higher ventral and dorsal core endurance (ES = 0.69, p = 0.07) and largely higher relative HR at the lactate thresholds (ES = 1.54, p < 0.01). The individual data of female players showed more variability. Some individual data of women overlapped those of men, most evident in the total core endurance and v2. The findings indicate that there are sex differences in physical capacities according to the underlying amount of anaerobic and aerobic energy supply. The sex specificities should be considered to optimize training and testing procedures for soccer players.